DNA methylation differences at the glucocorticoid receptor gene in depression are related to functional alterations in hypothalamic–pituitary–adrenal axis activity and to early life emotional abuse. (July 2018) - Farrell, Chloё; Doolin, Kelly; O' Leary, Niamh; Jairaj, Chaitra; Roddy, Darren; Tozzi, Leonardo; Morris, Derek; Harkin, Andrew; Frodl, Thomas; Nemoda, Zsófia; Szyf, Moshe; Booij, Linda; et al.
Abstract: Depression is associated with alterations in hypothalamic–pituitary–adrenal (HPA) axis activity. A proposed mechanism to explain these alterations are changes in DNA methylation levels, secondary to early life adversity (ELA), at stress-related genes. Two gene regions that have been implicated in the literature, the glucocorticoid receptor gene ( NR3C1 ) exon 1F and the FKBP5 gene intron 7 were examined in 67 individuals (33 depressed patients and 34 controls). We investigated whether cortisol concentrations, evaluated in 25 depressed patients and 20 controls, and measures of ELA were associated with the degree of methylation at these candidate gene regions. Mean NR3C1 exon 1F DNA methylation levels were significantly increased in the depressed cohort and the degree of methylation was found to be positively associated with morning cortisol concentrations. DNA methylation levels at specific CG sites within the NR3C1 exon 1F were related to childhood emotional abuse severity. DNA methylation at CG38 was related to both HPA axis and childhood emotional abuse measures in the depressed group. No FKBP5 differences were revealed. Our findings suggest that hypermethylation at the NR3C1 exon 1F may occur in depression. This locus-specific epigenetic change is associated with higher basal HPA axis activity, possibly reflecting acquired glucocorticoid receptor resistance.